Effects of a single initial and delayed release implant on arrival compared with a non-coated initial implant and a non-coated terminal implant in heifers fed across various days on feed. Issue 4 (12th August 2019) - Smith, Zachary K; Holland, Ben P; Word, Alyssa B; Crawford, Grant I; Nichols, Wade N; Nuttelman, Brandon L; Streeter, Marshall N; Hutcheson, John P; Johnson, Bradley J
Abstract: Two experiments evaluated the effect of implant number, type, and total steroidal dose on live animal performance and carcass traits in heifers fed for three different days on feed (DOF). In experiment 1, heifers ( n = 3, 780; 70 heifers/pen and 9 pens/treatment; initial body weight [BW] = 309 kg) were used in a 2 × 3 factorial arrangement of treatments. Factors were as follows: 1) implant (all from Merck Animal Health, De Soto, KS): 200 mg trenbolone acetate (TBA) and 20 mg estradiol-17β (E2 ) administered on arrival (SINGLE), or 80 mg TBA and 8 mg E2 administered on arrival followed by 200 mg TBA and 20 mg E2 after approximately 90 d (REPEATED) and 2) duration of DOF: harvested after approximately 172, 193, and 214. In experiment 2, heifers ( n = 3, 719; 65 to 70 heifers/pen and 9 pens/treatment; initial BW = 337 kg) were used with the same factors as experiment 1, except DOF were 150, 171, and 192. No implant × DOF interaction ( P ≥ 0.06) was noted for any performance parameters in either experiment. Heifers administered REPEATED had improved ( P ≤ 0.05) live gain to feed ratio (G:F) and carcass-adjusted G:F and tended ( P = 0.09) to have greater hot carcass weight (HCW) in experiment 1. Increasing DOF resulted in greater ( P ≤ 0.01) live and carcass-adjusted final BW and decreased ( P = 0.01) live ADG in experiment 1. As DOF increased, HCW, HCW gain, and dressing% ( P ≤ 0.01) increased in experiment 1. The mean carcass transfer was 79.6% across the 42 d terminal window in experiment 1. In experiment 2, REPEATED had improved ( P = 0.03) carcass-adjusted G:F compared with SINGLE, but HCW was not different ( P = 0.36) between treatments. Increased DOF resulted in greater ( P ≤ 0.01) final live and carcass-adjusted BW, decreased ( P ≤ 0.01) live and carcass-adjusted ADG, and poorer ( P ≤ 0.01) live and carcass-adjusted G:F in experiment 2. In experiment 2, dressing percentage was greater ( P = 0.02) in REPEATED compared with SINGLE. Heifers given SINGLE had greater ( P = 0.01) back fat and estimated empty body fat (EBF), whereas REPEATED had fewer ( P = 0.01) Yield Grade 4 carcasses and greater ( P = 0.01) longissimus muscle (LM) area. Increased DOF resulted in greater ( P ≤ 0.04) HCW, HCW gain, dressing%, back fat, LM area, marbling, EBF%, and United States Department of Agriculture (USDA) Prime-grading carcasses, Yield Grade 4 and 5, and over 454-kg carcasses in experiment 2. Carcass ADG and carcass transfer indicate a 0.70 kg carcass ADG between 150 and 192 DOF, resulting in an average carcass transfer of 72.2% in experiment 2. Although feedlot growth performance and HCW did not differ between the implant regimens tested, increasing DOF resulted in decreased live growth performance while increasing the proportion of USDA prime carcasses and HCW.